Explanation of A Framework for the Effective Implementation of E-Learning at Universities of Medical Sciences: A Mixed Exploratory Method - Zohrehsadat Mirmoghtadaie; Zeinab Shakiba; Sara Shafian; Soleiman Ahmady (Kerman University of Medical Sciences, 2023)
Background: E-learning is considered the most important technology that can support new teaching-learning approaches. The objective of e-learning is to provide the same access and create the same educational space for all learners at any point, and optimize the methods of presenting course content for deeper and more serious learning.Objectives: The present study was conducted to develop a standard framework for the effective implementation of e-learning in medical science education.Methods: This study was conducted in two phases in 2022 using a mixed exploratory method. In the first (qualitative) phase, the initial framework was obtained from a comparative review of existing literature. In the second (quantitative) phase, the calculated standards were prepared in the form of an online questionnaire and sent to 20 e-learning experts in medical sciences. After data analysis, a framework of e-learning standards were proposed.Results: Nine dimensions and 58 standards were approved as the framework of e-learning standards. The lowest and highest content validity ratio (CVR) based on the analyzes were reported to be 0.77 and 0.88, respectively. As a result, all dimensions and 58 standards were approved. Also, the intraclass correlation (ICC) between 0.75 and 0.90 showed good reliability and high agreement between experts.Conclusion: Using a standard framework to implement e-learning helps to improve the quality of e-learning courses in medical sciences and brings more trust from internal and external stakeholders in these courses. Therefore, it is necessary to focus on the field of education and attempt to make educational organizations work in the best way in any situation, such as the fact that the world has recently been exposed to the o COVID-19 pandemic which led to the tendency of universities to use it.